1994
DOI: 10.1002/1097-0142(19940615)73:12<3064::aid-cncr2820731227>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant t-cell lymphoma. Report of three cases and a review of the literature

Abstract: Background. Although 14% of the malignant lymphomas after organ transplantation are reported to be T‐cell lymphomas, only a few cases are described in the literature. Methods. The authors presented three new cases. They summarized the clinical data and analyzed histologic and immunochemical findings. The presence of Epstein‐Barr virus (EBV) and human T‐cell lymphoma type 1 (HTLV‐1) were investigated. T‐cell receptor (TCR) rearrangement was analyzed by Southern blot technique in two cases. Results. Two of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
32
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(35 citation statements)
references
References 24 publications
2
32
0
1
Order By: Relevance
“…Reduced immunosurveillance, chronic antigenic stimulation due to the graft, or a direct oncogenic effect of immunosuppressive drugs have all been suggested as possible mechanisms leading to T-cell lymphoma in transplant recipients (16).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced immunosurveillance, chronic antigenic stimulation due to the graft, or a direct oncogenic effect of immunosuppressive drugs have all been suggested as possible mechanisms leading to T-cell lymphoma in transplant recipients (16).…”
Section: Discussionmentioning
confidence: 99%
“…4 Literature review showed 7 previous patients who had T-ALL after solid organ transplant (Table 1). [7][8][9][10][11][12] There is ambiguity about the pathogenesis of T-cell posttransplant lymphoproliferative disorder, and there are no accepted diagnostic criteria. Therefore, this condition is rarely reported and inconsistently characterized.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Our patient did not respond to antiviral agents, ␥-globulin, or a chemotherapeutic agent. Donor T cell infusion has been reported to be effective for treating EBV-associated B cell PTLD after allogeneic HCT.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 PTLD are virtually always of B cell origin; PTLD of T cell origin is rare. [3][4][5] Also, while B cell PTLD are usually associated with Epstein-Barr virus (EBV) infection, most T cell PTLD are not associated with the EBV genome. [3][4][5] Three cases of T cell PTLD have been reported as occurring after allogeneic HCT, all unassociated with EBV infection; 3 T cell PTLD after autologous HCT has not been reported.…”
mentioning
confidence: 99%